A single‐center experience with early adoption of physiologic pacing approaches. (9th December 2021) - Oates, Connor P.; Kawamura, Iwanari; Turagam, Mohit K.; Langan, Marie‐Noelle; McDonaugh, Mary; Whang, William; Miller, Marc A.; Musikantow, Daniel R.; Dukkipati, Srinivas R.; Reddy, Vivek Y.; Koruth, Jacob S.
Abstract: Background: Increasing interest in physiological pacing has been countered with challenges such as accurate lead deployment and increasing pacing thresholds with His‐bundle pacing (HBP). More recently, left bundle branch area pacing (LBBAP) has emerged as an alternative approach to physiologic pacing. Objective: To compare procedural outcomes and pacing parameters at follow‐up during initial adoption of HBP and LBBAP at a single center. Methods: Retrospective review, from September 2016 to January 2020, identified the first 50 patients each who underwent successful HBP or LBBAP. Pacing parameters were then assessed at first follow‐up after implantation and after approximately 1 year, evaluating for acceptable pacing parameters defined as sensing R‐wave amplitude >5 mV, threshold <2.5 V @ 0.5 ms, and impedance between 400 and 1200 Ω. Results: The HBP group was younger with lower ejection fraction compared to LBBAP (73.2 ± 15.3 vs. 78.2 ± 9.2 years, p  = .047; 51.0 ± 15.9% vs. 57.0 ± 13.1%, p  = .044). Post‐procedural QRS widths were similarly narrow (119.8 ± 21.2 vs. 116.7 ± 15.2 ms; p  = .443) in both groups. Significantly fewer patients with HBP met the outcome for acceptable pacing parameters at initial follow‐up (56.0% vs. 96.4%, p  = .001) and most recent follow‐up (60.7% vs. 94.9%, p  ≤ .001; at 399 ± 259 vs. 228 ± 124 days, p  ≤ .001). More HBP patients required lead revision due to early battery depletion or concern for pacing failure (0% vs. 13.3%, at a mean of 664 days). Conclusion: During initial adoption, HBP is associated with a significantly higher frequency of unacceptable pacing parameters, energy consumption, and lead revisions compared with LBBAP.